DURABLE PROGRAM EXECUTION (2019)
Aspects of the subject matter described herein relate to durable program execution. In aspects, a mechanism is described that allows a program to be removed from memory when the program is waiting for an asynchronous operation to complete. When a response for the asynchronous operation is received, completion data is stored in a history, the program is re-executed and the completion data in the history is used to complete the asynchronous operation. The above actions may be repeated until no more asynchronous operations in the history are pending completion.